LINGUAPRAGMATIC FUNCTIONS OF PHRASEOLOGICAL UNITS IN ENGLISH - Sharifova , Ma’mura Bahodir qizi (Educational Research in Universal Sciences, 2022)
In this article Linguapragmatic functions of phraseological units in English are discussed. As a demand, it consists of annotation, keywords, introduction, main part, conclusion and reference.